ESG DISCLOSURE, RELATED PARTY TRANSACTIONS, AND EXECUTIVE CHARACTERISTICS ON TAX AVOIDANCE - Khusna, Khikmatul; Subandi, Hendi (Widya Mandala Surabaya Catholic University, 2025)
Research Purpose. This research aimed to gather empirical evidence on the impact of Environmental, Social, and Governance Disclosure, related-party transactions, and executive characteristics on tax avoidance, with company size and company age as control variables. Research Method. Secondary data was analyzed using multiple linear regression with SPSS. This research focuses on LQ45 companies listed on the Indonesia Stock Exchange from 2019 to 2022. The study includes a sample of 24 companies selected based on specific criteria through purposive sampling. Research Result and Findings. The findings reveal that Environmental, Social, and Governance Disclosure negatively impact tax avoidance; related-party transactions positively influence tax avoidance, while executive characteristics do not significantly affect tax avoidance. The model explains 38.8% of the tax variation, and the research implications support Agency Theory and Legitimacy Theory. The research implications, as such, suggest that companies make deliberate decisions on environmental, social, and governance disclosure and related-party transactions to improve their governance structures. This research also suggests that future researchers should provide additional factors such as deferred tax burden, dividend policy, or compensation for fiscal losses and test other objects such as the JII70 Index, IDX 80, or Kompas 100.